Effect of Enhanced Recovery After Surgery Protocol on Patients Who Underwent Off-Pump Coronary Artery Bypass Graft - Lin Chen; Jing Zheng; Dong Kong; Lijuan Yang (Elsevier, 2020)
Purpose: Enhanced recovery after surgery (ERAS) is an evidence-based perioperative measure to improve outcomes. Although the benefits of ERAS are well proven for other surgeries, little is known about its effect on off-pump coronary artery bypass graft (OPCABG) surgery. Thus, this study aimed to explore the effect of an ERAS protocol in patients who underwent OPCABG surgery. Methods: This quasi-experimental study included 94 participants (traditional care group = 47 vs ERAS group = 47). An ERAS protocol was established by a multidisciplinary team. Knowledge of coronary artery disease, fasting time, water deprivation time, extubation time of the tracheal tube and pericardial and mediastinal drainage tube, off-bed activity participation rate, length of hospital stay, hours of intensive care unit (ICU) stay, expenses in ICU, incidence rates of ICU delirium and postoperative nausea and vomiting, and the 6-Minute Walk Test on postoperative day 7 were recorded and calculated between the groups. Results: Demographics, lifestyle, and disease severity showed no significant difference between the two groups (p > .05). The ERAS group patients had improved understanding of coronary artery disease (t = −3.89, p < .01), shorter fasting time (t = 7.98, p < .01), shorter water deprivation time (t = 9.29, p < .01), increased off-bed activity participation (t = 17.67, p < .01), and the improved 6-Minute Walk Test on postoperative day 7 (t = −3.23, p < .01). Conclusions: The ERAS protocol is safe and effective for patients undergoing OPCABG surgery. Keywords: coronary artery bypass, early ambulation, thoracic surgery, walk test